Inner marginal strength of CAD/CAM materials is not affected by machining protocol. Issue 1 (1st January 2021) - Lubauer, Julia; Belli, Renan; Schünemann, Fernanda H.; Matta, Ragai E.; Wichmann, Manfred; Wartzack, Sandro; Völkl, Harald; Petschelt, Anselm; Lohbauer, Ulrich
Abstract: Purpose: Here we aimed to compare two machining strategies regarding the marginal strength of CAD/CAM materials using a hoop-strength test in model sphero-cylindrical dental crowns, coupled with finite element analysis. Materials and Methods: Five CAD/CAM materials indicated for single posterior crowns were selected, including a lithium disilicate (IPS e.max ® CAD), a lithium (di)silicate (Suprinity ® PC), a polymer-infiltrated ceramic scaffold (Enamic ® ), and two indirect resin composites (Grandio ® Blocs and Lava™ Ultimate). A sphero-cylindrical model crown was built on CAD Software onto a geometrical abutment and machined using a Cerec MC XL system according to the two available protocols: rough-fast and fine-slow . Specimens were fractured using a novel hoop-strength test and analyzed using the finite element method to obtain the inner marginal strength. Data were evaluated using Weibull statistics. Results: Machining strategy did not affect the marginal strength of any restorative material tested here. Ceramic materials showed a higher density of chippings in the outer margin, but this did not reduce inner marginal strength. IPS e.max ® CAD showed the statistically highest marginal strength, and Enamic ® and Lava™ Ultimate were the lowest. Grandio ® Blocs showed higher performance than Suprinity ® PC. Conclusions: The rough-fast machining strategy available in Cerec MC XL does not degrade the marginal strength of the evaluated CAD/CAD materials when compared to its fine-fast machining strategy. Depending on the material, resin composites have the potential to perform better than some glass-ceramic materials.